Characteristics of neutrophilic granulocytes of peripheral blood in patients with mechanical jaundice caused by cholangiocarcinoma - O. V. Smirnova; B. G. Gubanov; E. V. Kasparov; M. A. Darenskaya; L. I. Kolesnikova; S. I. Kolesnikov (Медицинская иммунология, 2022)
Obstructive jaundice caused by cholangiocarcinoma takes a special place among malignant disorders and surgical pathology in Russia. Involvement of nonspecific immunity and the role of neutrophils in carcinogenesis are ambiguously evaluated. The aim of this study was to study functional activity of peripheral blood neutrophilic granulocytes and their phenotype in obstructive jaundice caused by cholangiocarcinoma. The study included 56 patients with obstructive jaundice associated with cholangiocarcinoma at the T2- 3N0- 1M0 stage (clinical stages II-III), and 90 apparently healthy volunteers of similar age group. Neutrophilic granulocytes were isolated from peripheral blood by means of double-density Ficoll-Urografin gradient.Venous blood was collected in patients into vacutainers with heparin upon admission to the hospital, before the surgery was performed. Spontaneous cytokine production (IL-8, IFNá) was determined by enzyme-linked immunosorbent assay using Vector-Best diagnostic kits. To assess phagocytic activity of neutrophilic granulocytes, the phagocytic index (according to Hamburger), number of phagocytes (according to Wright) and the index of completed phagocytosis (according to Rudik, 2006) were calculated. Immunophenotyping of neutrophilic granulocytes was carried out using an FC500 flow cytometer (Beckman Coulter, USA) with monoclonal antibodies to CD11b+, CD16+, CD95+. The results were statistically analyzed using the Statistica v.12.0 software (StatSoft Inc., USA). To assess intergroup differences, the nonparametric Kruskal-Wallis tests (for three or more comparison groups) and Mann-Whitney tests (for pairwise comparison) were used. Comparison of groups for a qualitative binary trait was carried out using the two-sided Fisher’s exact test. Data are presented as Median (25 quartile-75 quartile).The study of the functional activity of peripheral blood neutrophiles in obstructive jaundice patients caused by cholangiocarcinoma revealed an increase in their relative and absolute number, increased phagocytic index and decreased phagocytic number of neutrophilic granulocytes, increased expression of CD11b+, CD16+, CD95+ immunological markers. The changes in neutrophil secretory activity were characterized by a decrease in cytokine production (IL-2, IFNá). An increase in functional activity of neutrophilic granulocytes, along with a decrease in their cytokine production suggests that, in obstructive jaundice observed in cholangiocarcinoma at clinical stage T2-3N0-1M0, an equilibrium stage is revealed between the cells of immune system and malignant tumor.